Superlattice-like alternating layered Zn2SiO4/C with large interlayer spacing for high-performance sodium storage. (1st May 2023) - Zhang, Minglu; Cheng, Dejian; Qiu, Guojian; Ning, Meng; Duan, Zhihua; Wan, Baoshan; Tang, Shuang; Miao, Lei; Li, Zhenghui; Zhang, Haiyan
Highlights: Zn2 SiO4 /C is designed by a simple one-pot hydrothermal intercalation strategy. Alternating layered contexture improves conductivity and stability. Zn2 SiO4 /C delivers a high reversible Na storage capacity and ultrafast energy output. The Na is stored through the reversible conversion between Zn2 SiO4 and Na x Zn. Abstract: Layered materials are among the most promising anode candidates for sodium-ion batteries, but suffer from limited interplanar spacing and poor electrical conductivity, resulting in unsatisfactory electrochemical performance. Herein, a novel layered composite of Zn2 SiO4 and carbon (Zn2 SiO4 /C) is designed by a simple one-pot hydrothermal intercalation strategy. The Zn2 SiO4 /C shows unique superlattice-like lamellar configuring that the Zn2 SiO4 layers and graphene-like carbon layers are alternately stacked, forming a sandwich-type structure. Such alternating layered contexture endows Zn2 SiO4 /C with improved conductivity and stability. In addition, the interplanar spacing of the Zn2 SiO4 /C achieves 1.44 nm, larger than most state-of-the-art layered materials, allowing the fast ion transfer from bulk electrolyte to the inner surface. As such, the Zn2 SiO4 /C delivers a high reversible Na storage capacity of 374 mAh g − 1, and it presents no visible capacity decline during the cycling test. More importantly, even under a very high current density of 20 A g − 1, the capacity remains 180 mAh g − 1, suggesting an ultrafast energy output within 33 s (≈109 C). The ex-situ studies show that Na storage of Zn2 SiO4 obeys a conversion−alloying mechanism, in which it is reduced to Zn, followed by the formation of Na x Zn alloy. Graphical abstract: Image, graphical abstract